Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1097/jto.0b013e318168f794
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with Gefitinib in Indian Patients

Abstract: Gefitinib seems well tolerated in Indian patients with advanced NSCLC, with some clinical benefit observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Fine tuning of the dose, co-prescription medication, extension of treatment schedule, and change to second-line therapy at the right time are part of the mid-course correction strategy that often do not get the importance they deserve. [34][35][36] …”
Section: Mid-course Correctionmentioning
confidence: 98%
“…Fine tuning of the dose, co-prescription medication, extension of treatment schedule, and change to second-line therapy at the right time are part of the mid-course correction strategy that often do not get the importance they deserve. [34][35][36] …”
Section: Mid-course Correctionmentioning
confidence: 98%
“…In a retrospective ad hoc analysis of 77 Indian patients included in the ISEL study, the median survival was observed to be 6.4 months with gefitinib and 5.1 months with placebo. The response rates were also better with gefitinib (14 vs. 0%) [32] .…”
Section: Unselected Populationmentioning
confidence: 66%
“…Parikh et al [32] analyzed 77 Indian patients enrolled in the ISEL study. The median survival and objective response rates in Indian patients were better with gefitinib compared to placebo (6.4 vs. 5.1 months; 14 vs. 0%).…”
Section: Experience From Indiamentioning
confidence: 99%
“…[26] Indian Study One retrospective analysis has found median survival of 6.4 months and response rates of 14% to geftinib in refractory advanced NSCLC in India. [27] …”
Section: Geftinib In Asian Populationsmentioning
confidence: 97%